2021
DOI: 10.3390/cells10040732
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rinsing Fluid during Negative Pressure Wound Therapy with Instillation: A Potential Monitoring Tool in Acute and Chronic Wound Treatment. A Pilot Study

Abstract: Background: During negative pressure wound therapy (NPWT), open wounds are draped with a nontransparent sponge, making daily wound evaluation impossible. Sometimes, late or undetected bacterial infections and postoperative bleeding result in repetitive surgery, thus prolonging inpatient time. With the introduction of additional fluid instillation (NPWTi), the wound surface is rinsed, and bacteria, proteins and biomarkers are flushed into a collecting canister, which is later discarded. Methods: The aim of this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Even though the pH of human skin surface ranges between 5.4 and 5.9, it was found to gradually increase with skin depth, and a pH close to neutral (pH 7.4) was observed after skin destruction in an acute wound [ 55 ]. The wound as scar tissue becomes acidic during healing and reestablishing the intact stratum corneum [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even though the pH of human skin surface ranges between 5.4 and 5.9, it was found to gradually increase with skin depth, and a pH close to neutral (pH 7.4) was observed after skin destruction in an acute wound [ 55 ]. The wound as scar tissue becomes acidic during healing and reestablishing the intact stratum corneum [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…NPWT stabilises the wound bed, promotes granulation, and improves local perfusion. Recently, it has been reported that NPWT promotes mechanical rinsing for bacterial decontamination through instillation [17][18][19][21][22][23][24]. However, deep and organ space infection of the pelvic cavity is anatomically di cult to access.…”
Section: Demographics and Clinical Featuresmentioning
confidence: 99%
“…Recently, mechanical rinsing for bacterial decontamination through instillation has been developed [17][18][19][21][22][23][24]. However, it is di cult to treat the soft tissue damage of an open pelvic fracture that is anatomically di cult to access, has many bends, and is located close to contamination sources, such as the anorectum [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that wound fluid contains locally produced and absorbed products, which provide insight into the wound-healing cascade [ 15 , 16 , 17 ]. Conventional negative pressure therapy in open abdominal wounds showed distinct clearance patterns of cytokines when compared with serum levels, thus allowing the investigation of abdominal sepsis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional negative pressure therapy in open abdominal wounds showed distinct clearance patterns of cytokines when compared with serum levels, thus allowing the investigation of abdominal sepsis [ 18 ]. Other studies evaluated the rinsing fluid of NPWT(i) devices and found that basic laboratory markers such as pH, electrolytes, and flow cytometry could safely be determined [ 16 ]. Increasing levels of polymorph nuclear cells marked the beginning of the inflammatory healing phase, and increased potassium values resembled cell destruction after surgical debridement [ 16 ].…”
Section: Introductionmentioning
confidence: 99%